Porifera from Ponta do Ouro (Mozambique) - Calcinai, Barbara; Belfiore, Giuseppe; Pica, Daniela; Torsani, Fabrizio; Palma, Marco; Cerrano, Carlo (European Journal of Taxonomy, 2020)
The diversity of Porifera from Ponta do Ouro (Mozambique) has been evaluated; this paper presents the first taxonomic effort devoted to sponges in the area, while studies of closeby areas are quite dated. Overall, 55 specimens were examined, leading to 26 described species; among these, four are new (Hyattella sulfurea Calcinai & Belfiore sp. nov., H. pedunculata Calcinai & Belfiore sp. nov., Amphimedon palmata Calcinai & Belfiore sp. nov. and Phoriospongia mozambiquensis Calcinai & Belfiore sp. nov.) and four (Chondrosia corticata Thiele, 1900, Callyspongia (Cladochalina) aerizusa Desqueyroux-Faundez, 1984, Clathria (Thalysias) hirsuta Hooper & Levi, 1993 and Ciocalypta heterostyla Hentschel, 1912) are new records for the Indian Ocean. For Callyspongia (Euplacella) abnormis Pulitzer-Finali, 1993, Callyspongia (Callyspongia) pulitzeri Van Soest & Hooper, 2020 and Amphimedon brevispiculifera (Dendy, 1905) this represents the first record after their initial discovery. The majority of the species have a wide distribution in the Indo-Pacific Ocean, but species from South and East Africa have also been recorded. These data highlight the characteristic of Ponta do Ouro as a transitional zone, located between a tropical and temperate biogeographic province, as well as the importance of increasing biodiversity knowledge of this biogeographic border to monitor possible shifts in the area as a consequence of climate crisis.